Integral Conditions for Convergence of Solutions of Non-Linear Robin's Problem in Strongly Perforated Domain - Khruslov, E.Ya.; Khilkova, L.O.; Goncharenko, M.V. (Журнал математической физики, анализа, геометрии, 2017)
We consider a boundary-value problem for the Poisson equation in a strongly perforated domain Ωε = Ω\Fε ⊂ Rⁿ (n ≥ 2) with non-linear Robin's condition on the boundary of the perforating set Fε. The domain Ωε depends on the small parameter ε > 0 such that the set Fε becomes more and more loosened and distributes more densely in the domain Ω as ε→0. We study the asymptotic behavior of the solution uε(x) of the problem as ε→0. A homogenized equation for the main term u(x) of the asymptotics of uε(x) is constructed and the integral conditions for the convergence of uε(x) to u(x) are formulated.